Palkkaerot palvelussia: Palvelualojen osa- ja kokoaikaisten työntekijöiden palkkarakenteen ja -kehityksen tarkastelua - Juha-Pekka Jokinen (The Research Institute of the Finnish Economy (ETLA), 2010)
This report studies differences in the wage structure between part-time and full-time employees in the service sector in 1990-2006. Using wage data from the registers of the Confederation of Finnish Industries, the report describes and compares wage distributions and their changes in the service sector. The analyses are carried out using both monthly and hourly incomes as well as regular earnings and total earnings. Moreover, many of the analyses are done separately for different industries. Thus, the report describes the key differences in the wage structure and wage differentials between part-time and full-time employees.
Keywords: 330; Lohnstruktur; Teilzeitarbeit; Dienstleistungssektor; Industrie; Finnland